Effect of Maritime Sector Reforms and Strategic Manpower Reorganization on Maritime Business Performance in Nigeria - University Ovuokeroye Edih; Mina Enaikpobomene Irejeh (Journal of Research in Environmental and Science Education, 2026)
Reforms are deliberate initiatives designed by the government or top management of an organization to effect some strategic improvements in the state or that particular institution. From a sectoral perspective, maritime reforms are geared towards facilitating the operational standards and developing the maritime sector to meet global benchmarks in efficient operations and management. Reforms are strategic policy thrusts consciously mobilized to grow the capabilities and core competencies of an economy. However, critical action plans have not been developed to attract investments in the maritime sector, and it has been discovered that the Nigerian maritime sector is grappling with several challenges that can only be addressed by strategic reforms. The objectives of the study are to boost government revenue, attract foreign direct investments (FDIs), sustain bilateral trade relations, and generate employment opportunities for the Nigerian population. The study considered measures that would assist the government and port administrators in overhauling the maritime sector, enhancing service delivery, attracting investments, and ensuring a secure environment for enterprising maritime businesses. It employed multiple regression analysis to analyze the primary data generated by administering a set of questionnaires. Multiple regression analyses were significant for the study because they accommodate more than one variable and do not alter the effects or results of individual variables. Findings revealed that maritime sector reforms and manpower reorganization have a positive and significant relationship with maritime performance. It was also affirmed that several challenges are impeding the performance of the industry in Nigeria, such as overbearing political interference, poor conditions of ports, a dearth of infrastructure, port congestion, and so on. The study recommends aggressive, strategic maritime reforms and a concrete manpower reorganization plan because the business world is fast-growing without considering nations that refuse to catch up with the dynamics associated with the growth process. Moreover, the growth process is accelerated by improved human knowledge and technological advancements.